Causal effects of human serum metabolites on occurrence and progress indicators of chronic kidney disease: a two-sample Mendelian randomization study - Yin, Yu; Shan, Conghui; Han, Qianguang; Chen, Congcong; Wang, Zijie; Huang, Zhengkai; Chen, Hao; Sun, Li; Fei, Shuang; Tao, Jun; Han, Zhijian; Tan, Ruoyun; et al. (Frontiers in Nutrition, 2024)
Background: Chronic kidney disease (CKD) is often accompanied by alterations in the body’s metabolic profile, yet the causative role of these metabolic changes in the onset of CKD remains a subject of ongoing debate. This study investigates the causative links between metabolites and CKD by leveraging genome-wide association study (GWAS) results from 486 blood metabolites, employing bulk two-sample Mendelian randomization (MR) analyses. Building on the metabolites that exhibit a causal relationship with CKD, we delve deeper using enrichment analysis to identify the metabolic pathways that may contribute to the development and progression of CKD. Methods: In conducting the Mendelian randomization analysis, we treated the GWAS data for 486 metabolic traits as exposure variables while using GWAS data for estimated glomerular filtration rate based on serum creatinine (eGFRcrea), microalbuminuria, and the Urinary albumin-to-creatinine ratio (UACR) sourced from the CKDGen consortium as the outcome variables. Inverse variance weighting (IVW) analysis was used to identify metabolites with causal relationship to outcome. Using Bonferroni correction, metabolites with more robust causal relationships are screened. Additionally, the IVW positive results were supplemented with the weighted median, MR Egger, weighted mode, and simple mode. We performed further sensitivity analyses using the Cochran Q test, MR-Egger intercept test, MR-PRESSO, and Leave One Out (LOO) test. Pathway enrichment analysis was conducted using two databases, KEGG and SMPDB, for eligible metabolites. Results: During the batch Mendelian Randomization (MR) analyses, upon completion of the Inverse Variance Weighted (IVW) approach, sensitivity analysis, and directional consistency checks, 78 metabolites were found to meet the criteria. The following four metabolites satisfy Bonferroni correction: mannose, N-acetylornithine, glycine, and bilirubin (Z, Z), and mannose is causally related to all outcomes of CKD. By pathway enrichment analysis, we identified 8 metabolic pathways that contribute to CKD occurrence and progression. Conclusion: Based on the present analysis, mannose met Bonferroni correction and had causal associations with CKD, eGFRcrea, Microalbuminuria, and UACR. As a potential target for CKD diagnosis and treatment, mannose is believed to play an important role in the occurrence and development of CKD.